2000
DOI: 10.1177/039463200001300109
|View full text |Cite
|
Sign up to set email alerts
|

Morning Sudden Cardiac Death

Abstract: A circadian variation of cardiac function with peak in the early morning was documented about twenty years ago. A circadian rhythm of platelet aggregability, in the same time of the day, was demonstrated in healthy young male subjects. The morning hours were also reported as crucial for sympathetic nervous system activity, for heart rate variability, and for the abrupt rise in blood pressure. Altogether, these trigger factors may explain the high incidence of sudden cardiac death during the morning.In the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Although the importance of neural mechanisms in the genesis of cardiac arrhythmias and onset of sudden cardiac death (SCD) has long been a topic of interest, 1 new findings have renewed expectations that improved understanding of cardiac neural connections will provide needed effective ways to treat and prevent ventricular arrhythmias and SCD. Diurnal changes in the occurrence of cardiac sudden death, for example, have been recognized, 2–4 and beta‐blocker use blunts the morning peak in SCD 5 . These findings and the results of several other basic and clinical studies suggest that the surge of sympathetic activity associated with wakefulness is important in ventricular arrhythmogenesis.…”
Section: Editorial Commentmentioning
confidence: 77%
“…Although the importance of neural mechanisms in the genesis of cardiac arrhythmias and onset of sudden cardiac death (SCD) has long been a topic of interest, 1 new findings have renewed expectations that improved understanding of cardiac neural connections will provide needed effective ways to treat and prevent ventricular arrhythmias and SCD. Diurnal changes in the occurrence of cardiac sudden death, for example, have been recognized, 2–4 and beta‐blocker use blunts the morning peak in SCD 5 . These findings and the results of several other basic and clinical studies suggest that the surge of sympathetic activity associated with wakefulness is important in ventricular arrhythmogenesis.…”
Section: Editorial Commentmentioning
confidence: 77%
“…43 However, most of these counts were typically lower than the analytic imprecision of the cell counter, suggesting that improvement in analyzer performance is advisable before definitive conclusions can be drawn. 44 Platelet aggregability also undergoes a clear circadian rhythm, 45 which led some authors to hypothesize that the greater risk of sudden cardiac death (SCD) in the first hours after awakening may be at least partially due to platelet hyperresponsiveness in the morning. [46][47][48] Undar et al 49 reported an increase of platelet activity measured as membrane expression of P-selectin on platelets by flow cytometry from 6:00 to 9:00 AM, which was followed by a decrease from noon to midnight.…”
Section: Circadian Variation Of Platelet Functionmentioning
confidence: 99%
“…Emerging experimental evidence suggests that calcium antagonists may block apoptosis in several cell lines (23,24) and in the kidney subjected to ischemia and reperfusion (25,26). The cardiovascular system is regulated by different paranmeters (27)(28)(29)(30)(31)(32)(33)(34)(35). There are however, few data regarding its effect during cardiac ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%